Producing deceptive actions in sports: The costs of generating head fakes in basketball - Güldenpenning, I.; Weigelt, M.; Böer, N. T.; Kunde, W. (Human Movement Science, 2023)
Typically, head fakes in basketball are generated to, and actually do, deteriorate performance on the side of the observer. However, potential costs at the side of the producer of a fake action have only rarely been investigated before. It is thus not clear yet if the benefit (i.e., slowed reactions in the observer) of performing a head fake is overestimated due to concurrently arising fake production costs (i.e., slowed performance in the producer of a head fake). Therefore, we studied potential head-fake production costs with two experiments. Novice participants were asked to generate passes to the left or right side, either with or without head fakes. In Experiment 1, these actions were determined by an auditory stimulus (i.e., a 440 Hz or 1200 Hz sinus or jigsaw wave). After an interstimulus interval (ISI) of either 0 ms, 800 ms, or 1500 ms, which served the preparation of the action, the cued action had to be executed. In Experiment 2, passing to the left or right, either with or without a head fake, was determined by a visual stimulus (i.e., a player with a red or blue jersey defending either the right or left side). After an ISI of either 0 ms, 400 ms, 800 ms, or 1200 ms, the cued action had to be executed. In both experiments, we observed higher reaction times (RTs) for passes with head fakes as compared to passes without head fakes for no and an intermediate preparation interval (from ISI 0 ms to 800 ms), but no difference for a long preparation interval (for an ISI of 1200 ms and 1500 ms). Both experiments show that generating fake actions produces performance costs, however, these costs can be overcome by a longer preparation phase before movement execution.